Interepidemic Rift Valley Fever Virus Seropositivity, Northeastern Kenya - LaBeaud, A. Desiree; Muchiri, Eric M.; Ndzovu, Malik; Mwanje, Mariam T.; Muiruri, Samuel; Peters, Clarence J.; King, Charles H. (Emerging infectious diseases, 2008)
Most outbreaks of Rift Valley fever (RVF) occur in remote locations after floods. To determine environmental risk factors and long-term sequelae of human RVF, we examined rates of previous Rift Valley fever virus (RVFV) exposure by age and location during an interepidemic period in 2006. In a randomized household cluster survey in 2 areas of Ijara District, Kenya, we examined 248 residents of 2 sublocations, Gumarey (village) and Sogan-Godud (town). Overall, the RVFV seropositivity rate was 13% according to immunoglobulin G ELISA; evidence of interepidemic RVFV transmission was detected. Increased seropositivity was found among older persons, those who were male, those who lived in the rural village (Gumarey), and those who had disposed of animal abortus. Rural Gumarey reported more mosquito and animal exposure than Sogan-Godud. Seropositive persons were more likely to have visual impairment and retinal lesions; other physical findings did not differ.